Kontribusi Antara Panjang Lengan Terhadap Keterampilan Servis Bawah Dalam Permainan Bola Voli Di SMK Negeri 5 Bengkulu Utara - Al Faruq; Dodi Ertanto; Asnawati Asnawati (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to determine the contribution of arm muscle strength to underhand service skills in volleyball games at SMK Negeri 5 Bengkulu Utara. This type of research is correlational research. The sample of the study was 20 people. The instruments used in this study were the pull-up test and the underhand service test in volleyball games. Where the results of the contribution of arm muscle strength to the underhand service test were 90.17%. With the discovery of a significant contribution of arm muscle strength to underhand service skills in volleyball games at SMK Negeri 5 Bengkulu Utara, arm muscle strength can be used as a tool to predict underhand service skills in volleyball games.